1986
DOI: 10.1093/brain/109.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy Associated With Hereditary Motor and Sensory Neuropathy

Abstract: Thirteen members of a large family presented with a hereditary motor and sensory neuropathy (HMSN); 8 of them also showed more or less prominent signs of myotonic dystrophy (MyD). There were no cases with MyD alone. The disorder showed segregation with genetic markers for the MyD gene on chromosome 19. This was also true for the 5 subjects in which clinically only HMSN had been detected, 3 of whom were young children. This is the first time that a form of HMSN has been found to be coded for by a gene localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…At the same time, controversy continues about whether PN in DM1 is primary or secondary to other causes such as diabetes or drugs. 3,4,[10][11][12] Patient 18 in this study was evaluated carefully to check for other possible causes of PN, such as metabolic, nutritional, or genetic factors, but we found no other causes of PN. An oral glucose tolerance test involving a 75 g glucose load showed normal fasting and postprandial serum glucose concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…At the same time, controversy continues about whether PN in DM1 is primary or secondary to other causes such as diabetes or drugs. 3,4,[10][11][12] Patient 18 in this study was evaluated carefully to check for other possible causes of PN, such as metabolic, nutritional, or genetic factors, but we found no other causes of PN. An oral glucose tolerance test involving a 75 g glucose load showed normal fasting and postprandial serum glucose concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…Until recently, it was thought that PN may coexist with DM1. 3,4,12 Some authors have insisted that PN is not uncommon and exists in 20%-30% of patients with DM1. [18][19][20][21] This thesis is supported by electrophysiological, 18,21,22 pathological, 20 and clinical findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are controversial results for the involvement of the peripheral nervous system in DM. Axonopathy was reported, involving both the motor and the sensory nerves, rather than demyelination in electrophysiological investigation of DM patients [4][5][6][7][8][9]. However, morphological and morphometric analyses of DM1 transgenic mice, carrying 300 CTG repeats, did not reveal axonal degeneration, sensory and motor neuropathy and a significant demyelination [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1986, we described 13 family members with clinical and electromyographic features of hereditary motor and sensory neuropathy, eight of them also exhibiting clinical or electromyographic signs of myotonic dystrophy. Genetic linkage studies with markers for chromosomes 1 and 19 strongly suggested that the disorder was caused by a single mutation at the DM1 locus, or by two closely linked mutations, on chromosome 19 3. In a follow-up study, 10 patients (nine from the original study and one additional patient) and 25 clinically unaffected relatives were investigated using recombinant DNA technology.…”
mentioning
confidence: 99%